2010
DOI: 10.2319/120808-619.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Level Laser Therapy and Orthodontic Tooth Movement on Dental Pulps in Rats

Abstract: Objectives:To describe the microscopic pulpal reactions resulting from orthodontically induced tooth movement associated with low-level laser therapy (LLLT) in rats. Materials and Methods: Forty-five young male Wistar rats were randomly assigned to three groups. In group I (n ϭ 20), the maxillary right first molars were submitted to orthodontic movement with placement of a coil spring. In group II (n ϭ 20), the teeth were submitted to orthodontic movement plus LLLT at 4 seconds per point (buccal, palatal, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
2
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 21 publications
1
24
2
6
Order By: Relevance
“…In this case, orthodontic treatment was continued successfully after 6 months. Findings of acceleration of new vascularization, 30 changes in cell proliferation, 30 increases in cellular proliferation of periodontal ligament cells, 27 and higher expression of fibroblast growth factors in the periodontal tissue 25 as reported in studies regarding low-power laser irradiation-associated orthodontic tooth movement might have played a role in the findings of this current study.…”
Section: Effect Of Low-level Laser On Extrusive Luxationsupporting
confidence: 54%
See 3 more Smart Citations
“…In this case, orthodontic treatment was continued successfully after 6 months. Findings of acceleration of new vascularization, 30 changes in cell proliferation, 30 increases in cellular proliferation of periodontal ligament cells, 27 and higher expression of fibroblast growth factors in the periodontal tissue 25 as reported in studies regarding low-power laser irradiation-associated orthodontic tooth movement might have played a role in the findings of this current study.…”
Section: Effect Of Low-level Laser On Extrusive Luxationsupporting
confidence: 54%
“…However, the fast occurring healing observed in the patient caused a change of mind, and the authors decided not to perform endodontic treatment and to continue with only the LLLT treatment. Abi-Ramia et al, 30 who studied the effects of LLLT and orthodontic tooth movement on dental pulps in rats, reported that LLLT leads to a faster repair of the pulpal tissue due to orthodontic movement. Orthodontically induced tooth movement associated with LLLT produced an increase in the vascularization, and this factor could accelerate pulp tissue repair.…”
Section: Effect Of Low-level Laser On Extrusive Luxationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the direction from dentin to tooth centre, pulp has four microscopic zones: odontoblast layer, cell-poor zone, cell-rich zone and pulp proper [2].…”
Section: Introductionmentioning
confidence: 99%